Cultural Characteristics and the Entrepreneurial Intentions of University Students - Bartha, Zoltán; S. Gubik, Andrea (Theory, Methodology, Practice – Review of Business and Management, 2017)
The goals of the paper are to analyse the relationship between the cultural dimensions and to investigate the entrepreneurial intentions and activity of university students in 21 selected OECD countries. The analysis was conducted using the GUESSS database, which also includes three cultural dimensions of the GLOBE project. We found that there is a positive correlation between the entrepreneurial intentions of students and In-Group Collectivism. Uncertainty Avoidance does not have a direct effect on entrepreneurial activity of intentions; however, it correlates positively with perceived behavioural control, which has been proved to have a significant effect on entrepreneurial intentions.